Answer:
1)3/4
2)3
3)12 MILES
4)2.5 pounds
5)5/8 pounds
am not sure but hopefully it helps you!!!!!!
Answer: 3
Step-by-step explanation:
y-3=2(x+1)
y - 3 = 2x + 2
+3. +3
y=2x+5
-1 is the x value so plug it in where the x is in the equation
y=2(-1) +5
y= -2 + 5
y= 3
Answer:
B. (-2,-4)
Explanation
Given equations:
y = 3x + 2
y = -2x - 8
Solving both equations will yield the values of x and y;
Solution:
y = 3x + 2 ----- (i)
y = -2x - 8 ------ (ii)
Using substitution method, input equation i, into ii
3x + 2 = -2x - 8
Collect like terms and solve;
3x + 2x = -8 -2
5x = -10
x = -2
Then put x = -2 into i, to find y
y = (-2 x 3) + 2
y = -6 + 2 = -4
So, the solution of the equation is B. (-2,-4)
Answer:
Drinks = 6.75
Popcorn= 1
Step-by-step explanation:
Let the popcorn = P
Let the drink = D
2*P + 3*D = 22.25 multiply this equation by 6
12*P + 4D = 39.00
<u>12P + 18D = 133.5</u> Subtract these two equations
- 14D = - 94.50 Divide by -14
-14D/-14 = -94.5/-14 Do the division
D = 6.75
=========================
12P + 4D = 39 Substitute for D
12P + 4*6.75 = 39 Combine
12P + 27 = 39 Subtract 27 from both sides
12P + 27-27=39-27 Collect like terms
12P = 12 Divide by 12
12P/12 = 12/12
P = 1 Answer
Answer: n = -4
3n - 3 = 4n + 1
Add 3 to both sides
3n = 4n + 4
Subtract 4n from both sides
-n = 4
Divide by -1 on both sides
n = -4